Fiscal Reconciliation of Commercial Financial Statements for Corporate Income Tax Calculation - Arvianda, Vivi; Prasaja, Mukti; Wibawa, Koerniawan Dwi; Nurrohman, Aan Dwi (Jurnal Cendekia Keuangan, 2025)
Introduction/Main Objectives: This research aims to determine the amount of corporate income tax for PDAM Ngawi Regency in 2021 after fiscal reconciliation. Background Problems: There are several components in the financial statements, such as depreciation of fixed assets, representation fees, and meeting consumption costs that do not follow tax provisions. This creates a difference between commercial profit and fiscal profit, which impacts the calculation of taxes payable. Novelty: Using BUMD as an object provides a new perspective in implementing fiscal reconciliation in entities owned by local governments. Research Methods: This research uses descriptive quantitative research. The data sources used are secondary data. The data analysis technique uses steps to make fiscal adjustments to the profit and loss report. Calculate fiscal net income by multiplying it by the corporate income tax rate to calculate the tax payable. Compare the calculation of corporate income tax payable between commercial and fiscal. Finally, the tax owed will be calculated, the differences identified, and the contributing factors will be concluded. Findings/Results: The results of this research indicate that income and expenses must be corrected. The results of the fiscal reconciliation caused operating profit to decrease to (Rp 195.368.629) or experience a loss because there was a positive fiscal correction of Rp. 507.193.723 and a negative fiscal correction of Rp 1.121.201.671. The income tax owed by PDAM Ngawi Regency in 2021 is included in nil because it experienced a fiscal loss of Rp 195.368.629.396, which will be compensated in the following year. Conclusion: Fiscal reconciliation of commercial financial statements shows that differences in accounting treatment and tax provisions cause compensable fiscal losses, so it is important to adjust financial statements following tax regulations to maintain compliance and accuracy in calculating taxes payable. Research limitation/implications: Inconsistencies in accounting treatment may lead to errors in calculating taxes payable, potentially resulting in sanctions or fiscal losses.